FairyWREN: A Sustainable Cache for Emerging Write-Read-Erase Flash Interfaces - McAllister, Sara; Wang, Sherry; Berg, Benjamin; Berger, Daniel S.; Amvrosiadis, George; Beckmann, Nathan; Ganger, G. R. (USENIX OSDI 2024, 2024)
Datacenters need to reduce embodied carbon emissions, particularly for ﬂash, which accounts for 40% of embodied carbon in servers. However, decreasing ﬂash’s embodied emissions is challenging due to ﬂash’s limited write endurance, which more than halves with each generation of denser ﬂash. Reducing embodied emissions requires extending ﬂash life-time, stressing its limited write endurance even further. The legacy Logical Block-Addressable Device (LBAD) interface exacerbates the problem by forcing devices to perform garbage collection, leading to even more writes. Flash-based caches in particular write frequently, limiting the lifetimes and densities of the devices they use. These ﬂash caches illustrate the need to break away from LBAD and switch to the new Write-Read-Erase iNterfaces (WREN) now coming to market. WREN affords applications con-trol over data placement and garbage collection. We present FairyW REN 1 , a ﬂash cache designed for WREN. FairyW REN reduces writes by co-designing caching policies and ﬂash garbage collection. FairyW REN provides a 12.5 × write reduction over state-of-the-art LBAD caches. This decrease in writes allows ﬂash devices to last longer, decreasing ﬂash cost by 35% and ﬂash carbon emissions by 33%.